A Novel Learning Model, Integration of Challenge-Based and Differentiated Learning: A Preliminary Study - Anak Agung Inten Paraniti; I Wayan Redhana; I Nyoman Suardana; Ketut Suma (Postgraduate, University of Mataram, 2024)
This research aims to explore the need to design a challenge-based learning model (CBLM) integrated with differentiated learning strategies (DLS). The result of this integration is called a differentiated challenge-based learning model (DCBLM). A descriptive research design (survey) was applied in this study. A total of 46 high school teachers who taught science classes (biology, chemistry, and physics) throughout Bali participated in this study. The research results showed that high school teachers have attempted to implement various innovative learning models. Five innovative learning models and their implementation problems were also found and discussed in this study. Teachers fervently hope that DCBLM will exist to enhance and maximize CBLM's assets. Regarding 21st-century learning, DCBLM is highly pertinent, and the Merdeka Curriculum is implemented in Indonesia to shape students’ character according to the Pancasila students’ profile